Balance ability and athletic performance - Hrysomallis, C. (Sports Medicine, 2011)
The relationship between balance ability and sport injury risk has been established in many cases, but the relationship between balance ability and athletic performance is less clear. This review compares the balance ability of athletes from different sports, determines if there is a difference in balance ability of athletes at different levels of competition within the same sport, determines the relationship of balance ability with performance measures and examines the influence of balance training on sport performance or motor skills.